2020
DOI: 10.1002/jmv.25989
|View full text |Cite
|
Sign up to set email alerts
|

A comparison study of SARS‐CoV‐2 IgG antibody between male and female COVID‐19 patients: A possible reason underlying different outcome between sex

Abstract: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in China at the end of 2019 has spread throughout the world and caused many thousands of deaths. The previous study reported a higher severe status rate and mortality rate in male patients in China. However, the reason underlying this difference has not been reported. The convalescent plasma containing a high level of

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
204
11
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(263 citation statements)
references
References 12 publications
30
204
11
18
Order By: Relevance
“…36 Additionally, females generated a stronger IgG production early on in the disease course compared with male patients, which is consistent with preexisting literature. 36…”
Section: The Potential Role Of the X-chromosomesupporting
confidence: 88%
See 1 more Smart Citation
“…36 Additionally, females generated a stronger IgG production early on in the disease course compared with male patients, which is consistent with preexisting literature. 36…”
Section: The Potential Role Of the X-chromosomesupporting
confidence: 88%
“…23,24,30,[32][33][34][35] In support of this, a study analyzing serum from 331 hospitalized patients found that most female patients with severe COVID-19 had more than 100 AU/mL of SARS-CoV-2 IgG antibodies, while most male patients had less than 100 AU/mL. 36 Additionally, females generated a stronger IgG production early on in the disease course compared with male patients, which is consistent with preexisting literature. 36…”
Section: The Potential Role Of the X-chromosomesupporting
confidence: 77%
“…Another study investigated IgG levels between male and female COVID-19 patients, stratifying patients by disease severity into mild, moderate, and severe status and into early, active, and recovery phases. While there was no significant difference in serum IgG levels across gender in mild and recovering patients, IgG levels in women were significantly elevated in the early disease phase and in severe cases ( 57 ). This situational increase in antibody titers cannot yet be determined as helpful or harmful in SARS, but it is worth noting for future investigation.…”
Section: Immune Responsementioning
confidence: 75%
“…Female individuals generally have stronger innate and adaptive immune responses than males, because the X-chromosome contains more copy numbers of immune-related genes [16]. A recent observation that the female patients have higher level of IgG antibody against SAES-CoV-2 compared with male patients [17], provides direct evidence for sex differences in immune responses. Severity of COVID-19 was de ned according to the diagnostic and treatment guideline for SARS-CoV-2 issued by Chinese National Health Committee (version 3-5).…”
Section: Discussionmentioning
confidence: 99%